1991
DOI: 10.1002/cbf.290090102
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus‐secretion coupling of arginine‐induced insulin release: Significance of changes in extracellular and intracellular pH

Abstract: The possible relevance of changes in extracellular and/or intracellular pH to the insulinotropic action of L-arginine and L-homoarginine was investigated in rat pancreatic islets. A rise in extracellular pH from 7.0 to 7.4 and 7.8 augmented the secretory response to these cationic amino acids whilst failing to affect the uptake of L-arginine by islet cells and whilst decreasing the release of insulin evoked by D-glucose. Under these conditions, a qualified dissociation was also observed between secretory data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In addition, an increase in plasma insulin concentration has been reported following the intravenous infusion of free amino acids in both healthy (7)(8)(9) and type 2 diabetic subjects (10). In accordance, various in vitro studies using incubated ␤-cells of the pancreas have described strong insulinotropic effects of arginine, leucine, and phenylalanine (11)(12)(13)(14)(15)(16)(17)(18). Recently, we performed a series of studies in which we determined the in vivo insulinotropic potential of various free amino acids and protein (hydrolysates) when ingested in combination with carbohydrates in healthy young subjects (19 -21).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, an increase in plasma insulin concentration has been reported following the intravenous infusion of free amino acids in both healthy (7)(8)(9) and type 2 diabetic subjects (10). In accordance, various in vitro studies using incubated ␤-cells of the pancreas have described strong insulinotropic effects of arginine, leucine, and phenylalanine (11)(12)(13)(14)(15)(16)(17)(18). Recently, we performed a series of studies in which we determined the in vivo insulinotropic potential of various free amino acids and protein (hydrolysates) when ingested in combination with carbohydrates in healthy young subjects (19 -21).…”
mentioning
confidence: 66%
“…Substantial progress has recently been made in the understanding of the mechanisms and signaling pathways by which leucine (12,(15)(16)(17), arginine (13)(14)(15)(16)30), and phenylalanine and its derivatives (18) stimulate ␤-cell function and insulin secretion in in vitro studies using isolated ␤-cells and insulinsecreting pancreatic ␤-cell lines. Clearly, the large responsiveness to the coingestion of the insulinotropic amino acid/protein mixture in the present study strongly suggests that amino acids can provide a glucose-independent stimulus to the pancreatic ␤-cells that is preserved in patients with long-term type 2 diabetes.…”
Section: Figure 2-plasma Glucose Concentration (A) and Response (B) Omentioning
confidence: 99%
“…transport (Collarini & Oxender 1987) and subsequent action on the cell. Although many studies have been performed to elucidate the mechanism of L-arginine-and L-leucine-induced insulin secretion (Henquin & Meissner 1981, Charles & Henquin 1983, Hermans et al 1987, Blachier et al 1989, Grapengeisser et al 1989, Malaisse et al 1991, the effects of many other amino acids including L-alanine, -aminoisobutyric acid and glycine are poorly understood, while others including L-proline and L-serine have been neglected.…”
Section: Discussionmentioning
confidence: 98%
“…Four free amino acids (leucine, phenylalanine, arginine, and glutamine) were tested. Several in vitro studies showed that these amino acids have a strong stimulating effect on insulin release by pancreatic ␤-cells (12)(13)(14)19). Floyd et al (5,7) observed that 30 g arginine injected intravenously in vivo in human subjects led to an equal insulin response as occurred with the mixture of 10 amino acids (30 g in total; arginine, lysine, phenylalanine, leucine, valine, methionine, histidine, isoleucine, threonine, and tryptophan).…”
Section: Discussionmentioning
confidence: 99%